Mouse models of ageing and their relevance to disease. (December 2016) - Kõks, Sulev; Dogan, Soner; Tuna, Bilge Guvenc; González-Navarro, Herminia; Potter, Paul; Vandenbroucke, Roosmarijn E.
Highlights: Different mouse models of ageing are available and provide insight into the pathogenic mechanisms of the ageing process. Genetic background and detailed phenotypic analysis of the available mouse models of ageing are important. There is an urgent need for the development of SOPs and standardized phenotyping in mice, across a range of physiological systems reflecting frailty as seen in patients. Several pathogenic processes can be modulated by caloric restriction in mouse models of ageing. Abstract: Ageing is a process that gradually increases the organism's vulnerability to death. It affects different biological pathways, and the underlying cellular mechanisms are complex. In view of the growing disease burden of ageing populations, increasing efforts are being invested in understanding the pathways and mechanisms of ageing. We review some mouse models commonly used in studies on ageing, highlight the advantages and disadvantages of the different strategies, and discuss their relevance to disease susceptibility. In addition to addressing the genetics and phenotypic analysis of mice, we discuss examples of models of delayed or accelerated ageing and their modulation by caloric restriction.